Pengaruh Fasilitas Kesehatan, Kualitas Pelayanan Perawat, Komunikasi Terapeutik Perawat Terhadap Kepuasan Pasien Diklinik Polres Seruyan 2026 - Ade Irawan; Yudied Agung Mirasa; Eko Winarti (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2026)
This study was motivated by the continued dissatisfaction of patients with health services related to the availability of facilities, the quality of nursing services, and the effectiveness of therapeutic communication during the treatment process. These conditions indicate that the quality of health services needs to be improved so that the services provided can optimally meet the needs and expectations of patients. Therefore, this study aims to analyze the effect of health facilities, nursing service quality, and therapeutic communication on patient satisfaction at Sidokkes Clinic, Seruyan Police Department. Patient satisfaction is a critical indicator in evaluating healthcare service quality, as it reflects the alignment between patient expectations and actual service performance. This research employed an analytic correlational design with a cross-sectional approach. A total of 100 respondents were selected using accidental sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS software. The results indicate that health facilities have a positive and significant effect on patient satisfaction (t = 5.739; p < 0.05), nursing service quality also has a positive and significant effect (t = 2.793; p < 0.05), and therapeutic communication shows a positive and significant effect (t = 6.458; p < 0.05). Simultaneously, the three independent variables significantly influence patient satisfaction (F = 154.645; p < 0.05). The coefficient of determination (Adjusted R²) of 0.823 indicates that 82.3% of the variation in patient satisfaction can be explained by these variables. Therapeutic communication emerged as the most dominant factor, with the highest standardized beta coefficient (0.495). It is concluded that improving the quality of healthcare services needs to focus on strengthening therapeutic communication supported by integrated facility management and nursing service quality in order to increase patient satisfaction.